Basophil Activation Test as a Biomarker for Taxanes Anaphylaxis - De Campos, Lucila; Giavina-Bianchi, Pedro; Acharya, Shree; Lynch, Donna-Marie; Kalil, Jorge; Castells, Mariana C. (Frontiers in Allergy, 2022)
Introduction: Taxanes are widely used chemotherapy agents, and their administration, despite premedication, is associated with hypersensitivity reactions in up to 9% of patients, 1% of which are severe. The mechanisms of these reactions are not fully understood. Finding biomarkers for early diagnosis and better understanding the underlying mechanisms of these reactions are key to defining the best treatment strategy for patients. Methods: The purpose of this study was to evaluate the effectiveness of the basophil activation test (BAT) to diagnose patients with anaphylactic reactions to taxanes. Patients with anaphylaxis to taxane compounds (n = 15) were assessed through clinical history, skin testing (when possible), and BAT. BAT was performed immediately before rapid drug desensitization or before skin testing to assess CD203c and CD63 expression on basophils under taxane stimulation. BAT was also performed in eight healthy volunteers. Results: BAT was positive for CD203c in eight out of 15 patients and for CD63 in four out of 15 patients and in two out of eight controls. The sensitivity for CD203c was 53%, the specificity was 87%, and the area under the curve was 0.66 (p = 0.19%). For CD63, these rates were 33%, 87%, and 0.6 (p = 0.4). In a subgroup analysis of patients with positive skin tests (11 patients), CD203c was positive in six patients (sensitivity of 54.5% and specificity of 87.5%), and CD63 was positive in five patients (sensitivity of 45% and specificity of 75%). Conclusions: BAT may help as a diagnostic tool in selected patients, particularly those who experience severe reactions and when the diagnosis cannot be established with skin testing. Increase of CD203c expression was more frequent than for CD63 expression, and the sensitivity of the test was higher in patients with positive skin tests